Hopes and realities : closing the gap between women's aspirations and their reproductive experiences - The Alan Guttmacher Institute (1995)
A guide to the report--The basic conditions of women's lives--Starting sexual relationships: marriage and living together--Family size: hopes and realities--Planning pregnancy and protecting reproductive health--Narrowing the gap.